Case report: Macrophage activation syndrome in a patient with Kabuki syndrome - Zhang, Jingyuan; Kang, Yuanbo; Xia, Zenan; Chong, Yuming; Long, Xiao; Shen, Min (Frontiers in Immunology, 2024)
Macrophage activation syndrome (MAS), is a severe and fatal complication of various pediatric inflammatory disorders. Kabuki syndrome (KS), mainly caused by lysine methyltransferase 2D (KMT2D; OMIM 602113) variants, is a rare congenital disorder with multi-organ deficiencies. To date, there have been no reported cases of MAS in patients with KS. This report describes a case of a 22-year-old male with Kabuki syndrome (KS) who developed MAS. This unique case not only deepens the understanding of the involvement of KMT2D in immune regulation and disease, but expands the phenotype of the adult patient to better understand the natural history, disease burden, and management of patients with KS complicated with autoimmune disorders.